Involvement of p38 mitogen‐activated protein kinase in altered expressions of AQP1 and AQP4 after carbon monoxide poisoning in rat astrocytes. Issue 4 (3rd June 2019) - Li, Jinlan; Jia, Min; Chen, Guiqin; Nie, Shuke; Zheng, Cong; Zeng, Weiqi; Xu, Yan; Wang, Congping; Cao, Xuebing; Liu, Qunhui
Abstract: Cerebral oedema is a major pathological change of acute carbon monoxide (CO) poisoning, the pathogenesis of which is still unclear. In the aquaporin (AQP) water channel family, AQP1 and AQP4 play critical roles in the progress of cerebral oedema of various neuropathological events. However, their functions in CO poisoning have not been demonstrated. In this study, we investigated the expressions of AQPs and associated mechanisms of brain injury in an acute CO poisoning rat model. Compared with the control injected intraperitoneally with equal volume of air, the dry weight/wet weight (DW/WW) ratio of brain water content, levels of AQP1, AQP4, phosph‐p38 mitogen‐activated protein kinase (p‐p38 MAPK) and astrocyte marker, glial fibrillary acidic protein (GFAP) in the frontal cortex and hippocampal CA1 of acute CO poisoning group significantly increased at 6, 12, 24 hours after CO injection. Intracerebroventricular injection with a p38 MAPK inhibitor, SB203580 (200 µmol/L/kg/d), before CO injection reduced water content in the brain tissues and significantly decreased levels of AQP1, AQP4, p‐p38 MAPK and GFAP. Therefore, our study showed that the overexpressions of AQP1 and AQP4 were involved in the development of CO poisoning‐induced cerebral oedema, which could be attenuated by inhibition of p‐p38 MAPK signalling. Manipulation of AQPs and p38 MAPK may be a new therapeutic strategy for acute CO poisoning.